2009
DOI: 10.1098/rsif.2009.0282
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on post-menopausal osteoporosis: establishing an interdisciplinary understanding of the sequence of events from the molecular level to whole bone fractures

Abstract: Current drug treatments for post-menopausal osteoporosis cannot eliminate bone fractures, possibly because the mechanisms responsible for bone loss are not fully understood. Although research within various disciplines has significantly advanced the state of knowledge, fundamental findings are not widely understood between different disciplines. For that reason, this paper presents noteworthy experimental findings from discrete disciplines focusing on post-menopausal osteoporosis. These studies have establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 154 publications
(181 reference statements)
2
68
0
2
Order By: Relevance
“…The results demonstrated that 4 weeks after treatment with LMWF, BMD was higher in the LMWF group when compared with the OVX group, and 8 weeks after surgery BMD increased further. BMD has been identified as an important factor for the evaluation of osteoporosis-related fractures; a previous study revealed that in accordance with BMD criteria, only 10-53% of patients are diagnosed with osteoporosis following an osteoporotic fracture (36). Micro-CT voxel-based test unit may be used for the early detection of lesions and bone structure deterioration (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that 4 weeks after treatment with LMWF, BMD was higher in the LMWF group when compared with the OVX group, and 8 weeks after surgery BMD increased further. BMD has been identified as an important factor for the evaluation of osteoporosis-related fractures; a previous study revealed that in accordance with BMD criteria, only 10-53% of patients are diagnosed with osteoporosis following an osteoporotic fracture (36). Micro-CT voxel-based test unit may be used for the early detection of lesions and bone structure deterioration (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Our results were in agreement with their reports. It is known that TNFĪ± and IL-6 are potent osteoclastogenic cytokines; the increased production of TNFĪ± and IL-6 can promote osteoclastogenesis and then stimulates bone loss [7,23] . TNFĪ± and IL-6 contain nuclear factor kappa B binding sites in their promoter, and when present in abundance, TNFĪ± and IL-6 can directly target osteoclast precursors to accelerate their differentiation and then increase osteoclast formation [11,24] .…”
Section: Discussionmentioning
confidence: 99%
“…the coordinated bone formation by osteoblasts and resorption by osteoclasts) were at first surprising. A recent study sought to establish the sequence with which complex changes in molecular and cellular biology, tissue composition, tissue integrity and architecture arise in the bone loss cascade of osteoporosis (McNamara 2010). It was proposed that the complex heterogeneous changes in bone tissue composition might be explained by the mechanical environment, which varies considerably in magnitude according to anatomical location.…”
Section: Introductionmentioning
confidence: 99%